Improved Analysis of Unstructured Datasets using Thesaurus Model - Kurian, Simy Mary; George, Neema; Sainudeen, Jinu P; John, Neethu Maria (International Journal of Computer Sciences and Engineering, 2019)
Humankind has put away in excess of 295 billion gigabytes (or 295 Exabyte) of information beginning around 1986, according to a report by the University of Southern California. Putting away and checking this information in generally disseminated conditions for all day, every day is an enormous errand for worldwide assistance associations. These datasets require high handling power which can't be presented by conventional information bases as they are put away in an unstructured arrangement. Although one can utilize Map Reduce worldview to take care of this issue utilizing java-based Hadoop, it can't give us with most extreme usefulness. Downsides can be defeated utilizing Hadoop-streaming methods that permit clients to characterize non-java executable for handling this dataset. This paper proposes a THESAURUS model which permits a quicker and more straightforward form of business examination.